From Risk Management to Healthcare Quality: The Role of Leadership Effectiveness-A Narrative Review - Aldahmashi, Amjad; Abdulsamad, Akram (Advances in Social Sciences Research Journal, 2026)
Risk management and leadership effectiveness are widely acknowledged as pivotal drivers of healthcare quality; however, the mechanisms through which they interact remain underexplored. This narrative review synthesizes current evidence on the relationships among risk management, leadership effectiveness, and healthcare quality, with particular emphasis on the mediating role of leadership effectiveness. Relevant literature was identified through systematic searches of Scopus, PubMed, Web of Science, and Google Scholar, covering English-language publications from 2012 to 2026. Following screening and eligibility assessment, 88 articles were included in the final review. The findings consistently indicate that effective risk management practices improve healthcare quality by enhancing patient safety, reducing adverse events, and strengthening organizational performance. More importantly, the review reveals that leadership effectiveness serves as a critical mediating mechanism, enabling risk management strategies to translate into meaningful quality improvements. Effective leaders foster a culture of safety, support informed decision-making, promote accountability, and facilitate the implementation of risk-informed practices across healthcare settings. By integrating these dimensions, this review advances the literature by developing a conceptual framework that explicates the interrelationships among risk management, leadership effectiveness, and healthcare quality. The review also underscores leadership effectiveness as a central organizational capability for achieving safer, more reliable, and higher-quality care. These insights provide an important foundation for future empirical research and offer practical implications for healthcare managers and policymakers seeking to strengthen quality outcomes through risk-sensitive leadership approaches.